Acute exercise preferentially redeploys NK-cells with a highly-differentiated phenotype and augments cytotoxicity against lymphoma and multiple myeloma target cells. Part II: Impact of latent cytomegalovirus infection and catecholamine sensitivity - Bigley, Austin B.; Rezvani, Katayoun; Pistillo, Mira; Reed, Justin; Agha, Nadia; Kunz, Hawley; O’Connor, Daniel P.; Sekine, Takuya; Bollard, Catherine M.; Simpson, Richard J. (Brain, behavior, and immunity, 2015)
•We investigated NK-cell responses to acute exercise in relation to CMV serostatus.•NK-cell redeployment after high intensity exercise is reduced in those with CMV.•CMV blocks the augmenting effect of exercise on NK-cell cytotoxicity.•CMV favors NK-cell subsets with poorly exercise responsive phenotypes.•NK-cell β-adrenergic receptor signaling is impaired in those with CMV. We showed previously that acute exercise is associated with a preferential redeployment of highly-differentiated NK-cells and increased cytotoxicity against HLA-expressing tumor cell lines during exercise recovery. In this part II study, we retrospectively analyzed these findings in the context of latent cytomegalovirus (CMV) infection and performed additional experiments to explore potential mechanisms underpinning the marked reduction in NK-cell redeployment with exercise in CMV-seropositive individuals. We show here that latent CMV infection impairs NK-cell mobilization with exercise, only when the intensity of the exercise bout exceeds the individual blood lactate threshold (BLT). This impaired mobilization is associated with increased proportions of poorly exercise-responsive NK-cell subsets (NKG2C+/KIR−, NKG2C+/NKG2A−, and NKG2C+/CD57+) and decreased NK-cell β2-adrenergic receptor (AR) expression in those with CMV. As a result, NK-cell production of cyclic AMP (cAMP) in response to in vitro isoproterenol (synthetic β-agonist) stimulation was drastically lower in those with CMV (6.0 vs. 20.3pmol/mL, p<0.001) and correlated highly with the proportion of NKG2C+/CD57+ NK-cells (R2=0.97). Moreover, NK-cell cytotoxic activity (NKCA) against the K562 (36.6% vs. 22.7%, p<0.05), U266 (23.6% vs. 15.9%, p<0.05), and 221.AEH (41.3% vs. 13.3%, p<0.001) cell lines was increased at baseline in those infected with CMV; however, latent CMV infection abated the post-exercise increase in NKCA as a result of decreased NK-cell mobilization. Additionally, NKCA per cell against the U266 (0.24 vs. 0.12, p<0.01), RPMI-8226 (0.17 vs. 0.11, p<0.05), and 221.AEH (0.18 vs. 0.11, p<0.05) cell lines was increased 1h post-exercise (relative to baseline) in CMV-seronegative subjects, but not in those infected with CMV. Collectively, these data indicate that latent CMV infection may compromise NK-cell mediated immunosurveillance after acute exercise due to an increased proportion of “CMV-specific” NK-cell subsets with impaired β-adrenergic receptor signaling pathways.